Investigation of the influencing factors with the uptake of the COVID‐19 vaccine booster dose among the general population of Ardabil, Iran: A cross‐sectional study - Nazila NeJhaddadgar; Mohammad Jafarzadeh; Zahra Khazir; Javad Yoosefi Lebni; Mohammad Rostami; Parisa Janjani; Arash Ziapour (Health Science Reports, 2023)
Abstract Background and Aims Vaccination is one of the most efficient approaches to combating COVID‐19 if it is adequately embraced by the general population. Numerous factors influence the uptake or refusal of the booster dose. The goal of this study was to look at the different factors that affect how the general population in Ardabil feels about getting vaccine boosters (annual boosters) for COVID‐19 and to evaluate those feelings. Methods and Materials In the city of Ardabil, general population, perceptions towards the COVID‐19 vaccine booster (annual boosters) dose were evaluated using a cross‐sectional survey design between January 2 and March 25, 2022. A questionnaire was developed and filled out by 662 subjects via phone calls from healthcare providers. Descriptive statistics, the Chi‐square test, the correlation coefficient, and regression analysis were run for the analysis of quantitative data. Results The findings of the research revealed that 238 participants, or 35.9%, had previously gotten the booster dose of the COVID‐19 vaccination, while 198 participants, or 29.2%, expressed a desire to do so as soon as feasible. A total of 187 (28.2%) respondents reported not wanting to get a booster dose, and 39 (5.7%) could not decide. In the factors found to affect decisions not to accept regular doses, adverse effects (45.4%) and the presence of misinformation (30%) were the most important. Regression in educational achievement, and following the COVID‐19 news showed to be the major predictors of the subjects' attitudes toward the regular COVID‐19 vaccine. Conclusion The present findings revealed that low confidence in the efficiency of the booster shot and misinformation are two critical factors to consider in educational planning and interventions.